Shared-role of vegetation types, elevation and soil affecting plant diversity in an old-tropical mountain hotspot - Loiola, Priscilla P.; Morellato, Leonor Patrícia Cerdeira; Camargo, Maria Gabriela Gutierrez; Kamimura, Vitor A.; Mattos, Jacqueline S.; Streher, Annia Susin; Le Stradic, Soizig (Journal of mountain science, 2023)
Despite the exceptional species richness and endemism, the environmental drivers of plant diversity along old tropical mountains remain under-explored. The respective importance of vegetation types, elevation, slope, and soil to drive diversity across life-forms is poorly addressed. Here, we tested whether environmental variables drove local and regional plant diversity along an old tropical mountain according to the three main life-forms: graminoids, herbaceous and woody species. We sampled all Angiosperm species on 180 plots across five elevations, at the tropical old-mountain region of Serra do Cipó, South-eastern Brazil. We assessed soil, slope, and vegetation types, and calculated richness and beta-diversity, applying generalized least square models, linear mixed-models and partial Mantel tests to test for relationships. Richness of graminoids and herbaceous species increased with greater elevation and more nutrient-impoverished soils, while woody richness showed the inverse pattern. Beta-diversity was primarily driven by species turnover, correlated with elevation and soil and higher in less dominant vegetation types, with unique species. Despite the limited elevational range in these old mountains, it still played an important role in filtering woody species, while fostering graminoid and herbaceous species. Conservation and restoration actions need to foster the high regional diversity supported by the old mountain heterogeneous landscape and the diversity of life-forms, especially the dominant and highly diverse grassy component.